ANALISIS PUSHOVER STRUKTUR BAJA PADA WILAYAH GEMPA KUAT (6) DENGAN STUDI KASUS STRUKTUR BANGUNAN BAJA BERATURAN - Iskandar Iskandar (Politeknik Negeri Lhokseumawe, 2013)
Criteria for earthquake resistant buildings are not only aware of the strength and ductility, but also on the performance of the building when the earthquake struck. To determine the behavior and performance of buildings, conducted research on building a 3D model of the building with a steel structure and a 5-story regular shapes by using an open frame structure system. The building was planned in accordance with the regulations for buildings steel SNI-03-1729 2002 and earthquake resistant building codes SNI 1726 – 2002. Building site is in a strong earthquake region (region 6). For performance evaluation was conducted using pushover analysis using SAP 2000 software, taking into account several design parameters, the drift ratio of the structure during a strong earthquake (X moot), shear force performance (Vbp). effective period structures (T ), effective of dumping structure (Red). Based on the analysis of the magnitude of the natural period of the structure is 0.748 seconds, the value is smaller than SNI 1726 - 2002 permit limits, so the structure is considered not very flexible, so the plan dimension of the structure is quite good. Shear force structure designed 3654.402 KN. Building performance evaluation results provide a target displacement in the X direction: 0.238 m and Y directions: 0.317 m, white according to SNI 1726 - 2002 gives the target displacement in the x direction: 0.338 m and y direction: 0,320 m. All values in the target displacement is a maximum value of 0.368 m (SNI 1726 - 2002).